Local guidelines for the transfer of women from midwifery unit to obstetric unit during labour in England: a systematic appraisal of their quality. - Rowe, R (2010)
BACKGROUND: A proportion of women planning to give birth in a midwifery unit will experience complications during labour that necessitate transfer to an obstetric unit. Local guidelines for the transfer of women in labour have the potential to impact on quality of care and the safety of the transfer process. OBJECTIVE: To systematically appraise the quality of local NHS guidelines on the transfer of women from midwifery unit to obstetric unit during labour. METHODS: Guidelines were requested from all 52 NHS hospital trusts in England with midwifery units. The Appraisal of Guidelines for Research and Evaluation Instrument was used to evaluate the quality of the guidelines received. RESULTS: Relevant guidelines were received from 34 (65%) trusts. No guidelines scored on the 'editorial independence' domain. The mean score on 'scope and purpose' (56.2%), concerned with the aims, clinical questions and target patient population of the guideline, was higher than for other domains: 'clarity and presentation' (language and format) 45.3%, 'stakeholder involvement' (representation of users' views) 15.3%, 'rigour of development' (process used to develop guideline) 15.0%, 'applicability' (organisational, behavioural and cost implications of applying guideline) 7.1%. Only three guidelines were recommended for use in clinical practice. CONCLUSIONS: We believe this to be the first systematic appraisal of the quality of local NHS guidelines. Overall these local guidelines were of poor quality. It is not clear whether the quality of these midwifery guidelines is typical of local guidelines in other clinical areas, but this study raises fundamental questions about the appropriate development of high-quality local clinical guidelines.